265 A PHYSIOTHERAPY-LED TRANSITION TO HOME INTERVENTION FOR OLDER ADULTS FOLLOWING EMERGENCY DEPARTMENT DISCHARGE: A PILOT FEASIBILITY RANDOMISED-CONTROLLED TRIAL. (25th October 2022) - Conneely, M; Holmes, A; O'Connor, M; Leahy, A; Gabr, A; Saleh, A; Okpaje, B; Corey, G; Barry, L; Griffin, A; O'Shaughnessy, Í; Ryan, L; et al.
Abstract: Background: Older adults frequently attend the Emergency Department (ED) and experience high rates of adverse outcomes following ED presentation including functional decline, ED re-presentation and unplanned hospital admission. The development of effective interventions to prevent such outcomes is a key priority for research and service provision. A presentation to an ED can be viewed as an opportunity to assess those at risk of adverse outcomes and initiate a care plan in those deemed as 'high risk'. Our aim was to evaluate the feasibility of a physiotherapy led integrated care intervention for older adults discharged from the ED (ED-PLUS). Methods: Older adults presenting to the ED with undifferentiated medical complaints and discharged within 72 hours were computer randomised in a ratio of 1:1:1 to deliver usual care, Comprehensive Geriatric Assessment (CGA) in the ED, or ED-PLUS (Trial registration: NCT04983602). ED-PLUS is an evidence-based and stakeholder-informed intervention to bridge the care transition between the ED and community by initiating a CGA in the ED and implementing a six-week, multi-component, self-management programme in the patient's own home. Feasibility (recruitment and retention rates) and acceptability of the programme were assessed quantitatively and qualitatively. Functional decline was examined post-intervention using the Barthel Index. All outcomes were assessed by a research nurse blinded to group allocation. Results: 29 participants were recruited, indicating 97% of our recruitment target. 90% of participants completed the ED-PLUS intervention. All participants expressed positive feedback about the intervention. The incidence of functional decline at 6 weeks was 10% in the ED-PLUS group versus 70-89% in the usual care and CGA-only groups. Conclusion: High adherence and retention rates were observed among participants and preliminary findings indicate a lower incidence of functional decline in the ED-PLUS group. Recruitment challenges existed in the context of COVID-19. Data collection is ongoing for six-month outcomes.